2010
DOI: 10.1007/s12088-010-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of mixed inoculum for methane enriched biogas production

Abstract: Inocula were collected from four different sources such as Jajmau tannery waste treatment plant (ITW), Jajmau municipal waste treatment (IMW), Unnao distillery (IDW) and a batch reactor, in which the sludge of a field scale biogas reactor was added to cow dung slurry to develop inoculum (IBS). A combination of these mixed inocula were used for biogas production at 35°C in laboratory scale reactor (10 L capacity) and the average yield of biogas (0.547 Lg(-1) volatile solid (VS)) and methane (0.323 Lg(-1)VS) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…For nitrogen, the biogas production is directly proportional to nitrogen concentration. Similar results were achieved by Singh et al (2010) which reported that the organic matter is reduced and converted to methane during anaerobic digestion of cattle waste slurry as substrate. The biogas produced was analyzed by gas chromatography, and substantial amount of methane was found in samples containing 4.5 mg/mL of nitrate as electron acceptor (90 %, Fig.…”
Section: Biogas Production With Different Electron Acceptorsupporting
confidence: 85%
See 2 more Smart Citations
“…For nitrogen, the biogas production is directly proportional to nitrogen concentration. Similar results were achieved by Singh et al (2010) which reported that the organic matter is reduced and converted to methane during anaerobic digestion of cattle waste slurry as substrate. The biogas produced was analyzed by gas chromatography, and substantial amount of methane was found in samples containing 4.5 mg/mL of nitrate as electron acceptor (90 %, Fig.…”
Section: Biogas Production With Different Electron Acceptorsupporting
confidence: 85%
“…In this case, the highest biogas production was obtained 9 days after incubation. The biogas production is comparable to those reported by Singh et al (2010) and Jackson-Moss and Duncan (1990), using cattle waste slurry and domestic sewage as the growth medium, respectively (0.10-0.51 L/L Day; this work 0.2-0.43 L/L Day), but lower compared with a mixed sludge that contains tannery sludge (1.49 L/L Day; Di Berardino and Martinho 2009). The least amount of biogas generated was in the treatment with the intermediate C/N ratio of 8, where very little or no amount of biogas was detected in any of the replicates throughout the incubation period.…”
Section: Variation In Organic Carbon and Organic Mattersupporting
confidence: 78%
See 1 more Smart Citation
“…Initially, 500 ml of microbial slurry along with 10% cow dung is taken for 2 kg of waste in the digester. Cow dung is efficient for this process of slurry formation as it comprises bacteria called "Estinia Fetida" which is responsible for the enhancement of forth formation process which is the initial stages to indicate the biogas production (Singh et al, 2010). After that, the ratios taken were 70% kitchen waste along with 20 % of microbes in aqueous form.…”
Section: Resultsmentioning
confidence: 99%
“…Jain, Dinesh kumar (2000), [6] carried studies on cattle dung and their residues insemination with kitchen waste and found that the increased biogas production using microbial stimulants. Ranjeet Singh, S. K. et.al [7]collected inocula from four different sources such as Jajmau tannery waste treatment plant (ITW), Jajmau municipal waste treatment (IMW), Unnao distillery (IDW) and batch reactor and carried studies for the generation of waste. Jong Won Kang et al (2010) [8]studied the On-site Removal of H2S from Biogas Produced by Food Waste using an Aerobic Sludge Bio filter for Steam Reforming Processing.…”
Section: IImentioning
confidence: 99%